(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Ionic contamination has become a serious environmental problem due to long-term disposal of untreated industrial effluent containing metal ions in river water ecosystem when applied to soil system as irrigation water. Considering this issue, an attempt was made to explore ionic contamination in water samples collected from the adjacent crop fields irrigated with the contaminated river during dry season towards food safety. Fifteen water samples were collected randomly from the upstream to downstream of the Bangshi river to determine ions in order to categorize these samples on the basis of their applicability for irrigation usage. The chemical analyses included pH, electrical conductivity (EC), total dissolved solids (TDS), cations (Ca, Mg, K, Na, Cd, Cr & Mn) and anions (CO3, HCO3, Cl & PO4). pH values of river water samples ranged from 6.5 to 7.6 indicating slightly acidic to slightly alkaline in nature. All the water samples were categorized as fresh water (TDS<1,000 mg L-1) in quality. River water samples were medium salinity (C2, EC=250-750 µS cm-1) hazard and were low alkalinity (S1, SAR<10) hazard expressing as C2S1. Regarding sodium adsorption ratio (SAR) values, samples were under excellent class (SAR<10) and as per soluble sodium percentage (SSP) values, all the samples were classified as permissible (SSP=40-60%) to doubtful (SSP=60-80%) classes. River water samples under consideration were free from residual sodium carbonate (RSC) and belonged to suitable (RSC<1.25 meq L-1) class. On the basis of hardness (HT), all the collected water samples were moderately hard (HT=75-150 mg L-1) in quality. Regarding the obtained permeability index (PI) values, water samples were under class-III implying 25% of maximum permeability when applied to soil system as irrigation water. The concentrations of Ca, Mg, K, Na, Cd, HCO3, Cl and PO4 in the studied water samples were within the acceptable limit and these ions were non-problematic for irrigation. Among the detected ions in river water samples, Cr and Mn ions were above the permissible limits for long-term irrigation usage and these ions were treated as chemical contaminants. The relationships between chemical quality parameters of river water such as EC, TDS, SAR, SSP, RSC, HT and PI were established. Among the combination, significant correlation was existed between SAR vs SSP, TDS vs RSC, SSP vs PI, RSC vs HT and RSC vs PI. Therefore, it is concluded from the present findings that among the detected ions, only two metals viz. Cr and Mn should be considered as chemical contaminants for long-term irrigation system towards food safety. J Bangladesh Agril Univ 18(1): 86–93, 2020 https://doi.org/10.5455/JBAU.79488